"Przewodnik polsko-angielski" Modesta Mariańskiego (1905) jako komunikat realizujący potrzeby komunikatywne polskich emigrantów w Stanach Zjednoczonych na początku XX wieku (rekonesans) = "Polish-english Guidebook" by Modest Mariański (1905) as a?message realizing communicative needs of polish emigrants in the United States of America at the beginning of the 20th century (reconnaissance) - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the linguistic means used in the English language textbook addressed to the Polish members of the "to earn the crust" emigration to build a sense of community and identity. The manual entitled "Polish-English Guidebook" was published in 1905 by an educated emigrant Modest Mariański.
Keywords: wspólnota komunikatywna; potrzeba komunikatywna; kształtowanie wspólnoty; język polski w Stanach Zjednoczonych w dobie rozbiorowej; emigracja "za chlebem"; Mariański, Modest (1854-1914); communicative community; communicative need; community formation; Polish language in the United States in the era of partition; emigration "to earn the crust"